A generic framework of three factor authentication with optional bio-metric or graphical password - Hossain, Mohammad Naveed; Zaman, Sheikh Fahim Uz; Khan, Tazria Zerin; Katha, Sumaiya Azad (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.